Effect on Procrastination and Learning of Mistakes in the Design of the Formative and Summative Assessments: A Case Study - Fidel Salas Vicente; Ángel Vicente Escuder; Miguel Ángel Pérez Puig; Francisco Segovia López (MDPI AG, 2021)
The design of the formative and summative assessment processes is of paramount importance to help students avoid procrastination and guide them towards the achievement of the learning objectives that are described in the course syllabus. If the assessment processes are poorly designed the outcome can be disappointing, including high grades but poor learning. In this paper, we describe the unexpected and undesirable effects that an on-demand formative assessment and the timetable of a summative assessment that left the most cognitively demanding part, problem-solving, to the end of the course, had on the behavior of students and on both grading and learning. As the formative assessment was voluntary, students procrastinated till the last minute. However, the real problem was that due to the design of the summative assessment, they focused their efforts mainly on the easiest parts of the summative assessment, passing the course with ease, but achieving a low learning level, as evidenced by the low scores of the problem-solving part of the summative assessment.